ANALISIS DAMPAK INFRASTRUKTUR TRANSPORTASI DAN TEKNOLOGI INFORMASI KOMUNIKASI TERHADAP NILAI TUKAR PERDAGANGAN DI ASEAN DAN ASIA TIMUR - Mimik Nurjanti; Dedi Budiman Hakim; Sri Mulatsih (IPB University, 2013)
The cooperation among ASEAN countries and East Asia countries gives advantage and challenge for each member country. Each country can improve their term of trade through international trade. The aims of this study are to analyze the impact of transportation infrastructure and information communication technology on term of trade in ASEAN countries (consist of Indonesia, Thailand, Singapore, Malaysia, Philipines and Vietnam) and East Asia countries (consist of China, Japan, Hongkong and South Korea). This study used panel yearly data of term of trade, index of transportation infrastructure, cost of export/import, time to export/import, internet user, and export/import of communication devices. Time references were 2006-2011. Statics panel data model was used to determine the relationship between term of trade and these variables for ASEAN and East Asia. Dummy intercept was applied to explain the differences between ASEAN countries and East Asia countries. The results expose that both in ASEAN and East Asia Countries, transportation infrastructure and the export value of communication devices have a positive correlation on the term of trade, whereas cost of export has a negative correlation on term of trade. To increase the term of trade, each country should be improve the quality of transportation infrastructure, increase export of communication devices,and reduce the cost to export. Keywords: term of trade, transportation infrastructure, information/communication devices, static panel data model